Le poste de travail pour traducteur de l’an 2015 – l’exemple de l’environnement traductionnel de la Direction générale de traduction de la Commission européenne - Walicka, Anna (Studia Romanica Posnaniensia, 2016)
The aim of this article is to provide an answer to the question about the current state of advancement of computer-assisted translation tools. We assume that several decades of research in the field carried out by the EU institutions in the context of the European integration process have provided the most advanced computer-assisted translation tools available in the biggest translation service in the world, i.e., the Directorate General for Translation of the European Commission. The present work therefore focuses on the following three main types of CAT tools employed by the EU translators: translation memory tools, terminology management tools and machine translation tools. The same types of tools, offered by the EU providers, i.e. SDL and SYSTRAN, are also used by translators working outside the EU structures. We can therefore presume that the EU translation services set work standards which are then accepted by all professional translators. For that reason, in order to define the most probable directions of future development of these tools, this article also reports the current research conducted by the EU in the CAT tools field.